Few-layer antimonene electrical properties. (September 2021) - Ares, Pablo; Pakdel, Sahar; Palacio, Irene; Paz, Wendel S.; Rassekh, Maedeh; Rodríguez-San Miguel, David; Aballe, Lucía; Foerster, Michael; Ruiz del Árbol, Nerea; Martín-Gago, José Ángel; Zamora, Félix; Gómez-Herrero, Julio; et al.
Highlights: Experimental characterization of few-layer antimonene electrical properties. Few-layer antimonene electrical transport seems to be independent of the thickness. Theory indicates that topologically protected surface states are playing a role. Abstract: Antimonene -a single layer of antimony atoms- and its few layer forms are among the latest additions to the 2D mono-elemental materials family. Numerous predictions and experimental evidence of its remarkable properties including (opto)electronic, energetic or biomedical, among others, together with its robustness under ambient conditions, have attracted the attention of the scientific community. However, experimental evidence of its electrical properties is still lacking. Here, we characterized the electronic properties of mechanically exfoliated flakes of few-layer (FL) antimonene of different thicknesses (∼ 2–40 nm) through photoemission electron microscopy, kelvin probe force microscopy and transport measurements, which allows us to estimate a sheet resistance of ∼ 1200 Ω sq −1 and a mobility of ∼ 150 cm 2 V −1 s −1 in ambient conditions, independent of the flake thickness. Alternatively, our theoretical calculations indicate that topologically protected surface states (TPSS) should play a key role in the electronic properties of FL antimonene, which supports our experimental findings. We anticipate our work will trigger further experimental studies on TPSS in FL antimonene thanks to its simple structure and significant stability in ambient environments. Graphical abstract: Image, graphical abstract